Ending Uncertainty: Recapitalisation of Banks Supervised by the SSM - Silvia Merler; Guntram B. Wolff (Credit and Capital Markets – Kredit und Kapital, 2014)
The European financial system is plagued at present by two major sources of uncertainty. First, there is still mistrust over the quality of banks" balance sheets. Second, major uncertainty remains about the rules that will apply to bank recapitalisation, bank restructuring and bank resolution in 2014 and in years to come. The fact that the European Central Bank is due to become the single supervisor for euro-area banks, and that it will conduct a far-reaching preliminary assessment of banks" balance sheets, has the potential to greatly reduce the first uncertainty, because a centralised assessment will make balance-sheet information more transparent, comparable and credible. In this paper, we look at the open question related to this fundamental step in the construction of the European Banking Union, highlighting the challenges and offering suggestions about the policy priorities. – – Das Ende der Unsicherheit: Rekapitalisation von Banken unter dem einheitlichen Bankenaufsichtsmechanismus (SSM) Zwei Unsicherheiten plagen das europäische Bankensystem derzeit. Erstens herrscht noch Misstrauen über die Qualität der Bankbilanzen und zweitens gibt es noch Unsicherheiten bezüglich der Leitrichtlinien zu Bankenrekapitalisierung, Bankenrestrukturierung und Bankenabwicklung die ab 2014 gelten werden. Die Tatsache, dass die Europäische Zentralbank die Bankenaufsicht des Euroraums in naher Zukunft übernimmt und dass sie eine weitreichende vorläufige Bewertung der Bankbilanzen vornimmt, hat das Potenzial die erste Unsicherheit massiv zu verringern, da eine zentralisierte Bewertung der Bankbilanzen zu mehr Transparenz, Vergleichbarkeit und Glaubwürdigkeit führen könnte. In diesem Aufsatz analysieren wir die noch offenen Fragen bezüglich dieses wesentlichen Schrittes zur Konstruktion der europäischen Bankenaufsicht, ihren Herausforderungen und unterbreiten Vorschläge für wirtschaftspolitische Prioritäten.
Keywords: G21; G28; E5; 330; Banking Union; ECB; banking supervision; stress tests